What is the role of the neutrophil extracellular traps in the cardiovascular disease burden associated with hemodialysis bioincompatibility? - Cristol, Jean-Paul; Thierry, Alain R.; Bargnoux, Anne-Sophie; Morena-Carrere, Marion; Canaud, Bernard (Frontiers in Medicine, 2023)
Despite significant progress in dialysis modalities, intermittent renal replacement therapy remains an “unphysiological” treatment that imperfectly corrects uremic disorders and may lead to low-grade chronic inflammation, neutrophil activation, and oxidative stress due to repetitive blood/membrane interactions contributing to the “remaining uremic syndrome” and cardiovascular disease burden of hemodialysis patients. Understanding dialysis bioincompatibility pathways still remains a clinical and biochemical challenge. Indeed, surrogate biomarkers of inflammation including C-reactive protein could not discriminate between all components involved in these complex pathways. A few examples may serve to illustrate the case. Cytokine release during dialysis sessions may be underestimated due to their removal using high-flux dialysis or hemodiafiltration modalities. Complement activation is recognized as a key event of bioincompatibility. However, it appears as an early and transient event with anaphylatoxin level normalization at the end of the dialysis session. Complement activation is generally assumed to trigger leukocyte stimulation leading to proinflammatory mediators’ secretion and oxidative burst. In addition to being part of the innate immune response involved in eliminating physically and enzymatically microbes, the formation of Neutrophil Extracellular Traps (NETs), known as NETosis, has been recently identified as a major harmful component in a wide range of pathologies associated with inflammatory processes. NETs result from the neutrophil degranulation induced by reactive oxygen species overproduction via NADPH oxidase and consist of modified chromatin decorated with serine proteases, elastase, bactericidal proteins, and myeloperoxidase (MPO) that produces hypochlorite anion. Currently, NETosis remains poorly investigated as a sensitive and integrated marker of bioincompatibility in dialysis. Only scarce data could be found in the literature. Oxidative burst and NADPH oxidase activation are well-known events in the bioincompatibility phenomenon. NET byproducts such as elastase, MPO, and circulating DNA have been reported to be increased in dialysis patients more specifically during dialysis sessions, and were identified as predictors of poor outcomes. As NETs and MPO could be taken up by endothelium, NETs could be considered as a vascular memory of intermittent bioincompatibility phenomenon. In this working hypothesis article, we summarized the puzzle pieces showing the involvement of NET formation during hemodialysis and postulated that NETosis may act as a disease modifier and may contribute to the comorbid burden associated with dialysis bioincompatibility.